Exsploring the Madurese political culture in the short story Pelean Klebun by Ahmad Suipardi - Faizin, Faizin; Isnaini , M.; Hang, Nguyen Thi Thu (Universitas Ahmad Dahlan, 2025)
This study aims to analyze the dynamic interplay between social structures and individual agents in Madurese political culture as depicted in Achmad Supardi's short story “Pelean Klebun” and the representation of Madurese culture in its political culture. The research used qualitative method with a sociological approachbased on Anthony Giddens. The results of this study reveal the depiction of the duality of structuration in the relationship between structure and agents in recursive and decursive forms. The recursive structure reinforces traditional power hierarchies by positioning established elites (blater, kiai, Klébun) in political processes, while the decursive structure represents countervailing democratic principles that theoretically allow non-elites to participate in village head elections. The representation of Madurese political culture in this literary work is depicted through the social background of Madura and its various phenomena, including the defense of dignity in village head elections.